Implementing electrical resistivity tomography to delineate soil contamination zone, Southern Baqubah City, Iraq: DOI: 10.48129/kjs.10674 - AL-Awsi, Munther Dhahir; Abdulrazzaq, Zaidoon Taha (Kuwait Journal of Science, 2022)
The electrical method is one of the most successful geophysical methods in identifying and evaluating the subsurface pollution area, in addition to the ease of applying its surveys and their low cost. An electrical resistivity tomography (ERT) survey was carried out in diyala university campus, southern Baqubaa city, Iraq. The main objective of this study was to evaluate the efficiency of ERT for buried sewage system detection as well as to assess the environmental impact of this system on the surrounding soil. Six parallel resistivity profiles were carried out at perpendicular direction to the axis of the sewage system, where six holes were drilled to collect soil samples for heavy metals concentrations analysis. 2D and 3D geoelectrical models were constructed to determine the distribution of resistivity and its relation with both buried structures and contaminated zones. The ERT results showed relative intermediate resistivity zone between 13m-16m distance, indicate the buried sewage system. Several rounded low resistivity zones (> 1 ohm.m) at a location close to both sides of the septic tank, were also shown in the clay layer. These zones may be representing the contaminated soil based on its very low resistivity and clayey material. The results of Chemical analysis showed a higher concentration of heavy metals near the septic system than area away from it. Much lower resistivity zones (<1 ohm.m) and the higher concentration of heavy metals observed near septic system indicate the impact of contamination by migration from the septic tank into the nearby soil. The results of this study confirm the efficiency of ERT for detecting a buried object and mapping contaminated zone for engineering and environmental applications.